Reviewing and Analyzing the Services of the Rulers of the Mashashian Government in the Territory under Their Rul - Mohammad Ahmadi Moghadam, Seyed; Abbas Mahdavi fard, Amir (International Journal of Psychosocial Rehabilitation, 2020)
The beginning of the Moshashaian movement in 840 AD led to the formation of the Moshashaian government by Sayyid Mohammad Falah in Khuzestan. During the reign of Moshashaian, which lasted for about 400 years, this government went through many ups and downs and took a lot of action in different areas of the land. However, there are different interpretations and disagreements with regard to the issues and their actions, which necessitates a comprehensive research in this regard. Therefore, this research tries to explore the role and influence of cultural and civilization of Moshashaian in Khuzestan by using a descriptive method. Studies show that in during of Moshashaian in Khuzestan, they were source of changes in religious, cultural and civilization, and they were able to engage in religious, religious, cultural, scientific, political and economic activities in accordance with the influences in the field of cultural and civilization in the land.